EXPLORATION OF LIVING QUR'AN IN MATTAMPUNG TRADITION OF THE BUGIS COMMUNITY: A STUDY IN BARUGAE, BONE, SOUTH SULAWESI - Iin Parninsih; Muhammad Alwi HS (International Conference on Social and Islamic Studies, 2021)
This paper examines Mattampung tradition in the Bugis community which is analyzed usingthe Living Qur'an lens. The Living Qur'an study is a study of the Qur'an but does not rely onits textual side, but on social phenomena that are born related to the presence of the Qur'an insociety. Meanwhile, Mattampung tradition is a tombstone planting ceremony as a substitutefor the tombstones that are planted when the body is buried. In this tradition, khatam al-Qur'an and tahlil are carried out. This tradition is carried out with the hope that all prayersfrom the community will reach the person who died so that he is given a quiet place by hisside. This study focuses on Barugae village community, Bone, South Sulawesi. The methodused is the ethnographic method, which is a qualitative design in which the researcherdescribes and interprets the same patterns of values, behavior, beliefs and language of a groupwith the same culture. The results of this study indicate that the implementation ofMattampung tradition is a form of local community reception of the glory of completing theQur'an and the suggestion to pray for the dead. Khatam al-Qur'an in this tradition occupies avery important position, especially as a complement to the implementation of Mattampungtradition. Thus, this tradition becomes a place for the local community to send prayers andcomplete the Qur'an with the aim that the reward of the prayer and completion can reach theperson who died and can make it easier for him in his next life.